Bioethics and nursing: The moral sense of taking care. Considerations of nursing ethics. - Sala, R. (Medicina e Morale, 2000)
The investigation about care and about the relationship among the actors of care, points out some fundamental elements of nursing as a practice of care. Care is the perspective in which the nurse-patient relationship takes place. It is characterized by the aim of taking care of the person, seeking the "right" answers to her individual needs. Care takes place in a particular context, in a special situation, determined by the uniqueness of personal experiences of the person who needs care. The focus on the relationship and context is central to the ethics of care; it permits to refer to the debate on nursing ethics, its peculiarity and distance from bioethics, especially from the methods of principles, too much abstract and ineffective. Accepting some suggestions coming from feminist theories, nursing ethics points out of the role of virtue, the practical meaning of acting, the relational dimension on it.